Cultural Product Design with the Doctrine of the Mean in Confucian Philosophy. (4th May 2018) - Chai, Chunlei; Shen, Danni; Bao, Defu; Sun, Lingyun
Abstract: Cultural products that adhere to the Doctrine of the Mean in Confucian philosophy have high commercial and cultural value. However, they are challenging to design and are seldom studied owing to the intangibility of the concept of culture. In this paper, we explore the applicability of this doctrine to product design, propose a design process in this vein, and use a chair as a case study to illustrate it. The doctrine is interpreted through five factors from three perspectives and is then converted into design elements based on which designers created the prototype of a chair. The results verified the effectiveness of the proposed method and the viability of design for infusing products with this aspect of Confucian culture. This extraction of design elements from similar and fused culture provides a novel method for designers to create cultural products.